Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Penggunaan SPaylater pada Generasi Z di Kecamatan Magersari Kota Mojokerto - Dwi Silvialorensa, Dina; Hartono, Hartono; Heru Dwihandoko, Toto (Ebisnis Manajemen, 2024)
Researchers know that many generation Z use SPaylater to make purchase transactions on the Shopee application. The types of products purchased are not all basic necessities, but they follow current trends and some even buy items because they are cute. The use of SPaylater can be influenced by the lifestyle of generation Z who follow trends without measuring their abilities. Therefore, financial literacy is really needed by society, especially generation Z. From this background, this research was conducted with the title "The Influence of Financial Literacy and Lifestyle on the Use of SPaylater in Generations Z in Magersari District, Mojokerto City." This research uses quantitative research methods and primary data collection is carried out using data collection techniques through distributing questionnaires using Google Form. Sampling method The researcher chose to use Purposive Sampling. In this research, the technique used to determine the sample size was the Solvin technique and resulted in a sample size of 389 respondents. The results of this research show that financial literacy has a significant effect on the use of spaylater. Lifestyle has a significant influence on the use of spaylater. Financial literacy and lifestyle together have a significant effect on spaylater use.